2023
DOI: 10.1002/bte2.20220052
|View full text |Cite
|
Sign up to set email alerts
|

Degradation mechanism of all‐solid‐state lithium‐ion batteries with argyrodite Li7−xPS6−xClx sulfide through high‐temperature cycling test

Abstract: Sulfide‐based all‐solid‐state lithium‐ion batteries (LIBs) are promising replacements for conventional liquid electrolyte LIBs. However, their degradation mechanisms and analysis methods are poorly understood. Herein, the degradation mechanism of an argyrodite‐type sulfide‐based all‐solid‐state prototype LIB cell is reported. Furthermore, an analysis method for all‐solid‐state batteries using charge/discharge cycle tests at 100°C followed by the disassembly analysis of cells before and after accelerated degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…A sudden voltage drop can be the signature of the direct electrical shorting of a battery. As high temperatures accelerate chemical degradation, the marginal voltage drop is also expected in ASLIBs . As shown in Figure a, the SSE-ASLIB exhibits a slow voltage drop at 160 °C; notably, the voltage drop is not as rapid as in the LE-LIB.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…A sudden voltage drop can be the signature of the direct electrical shorting of a battery. As high temperatures accelerate chemical degradation, the marginal voltage drop is also expected in ASLIBs . As shown in Figure a, the SSE-ASLIB exhibits a slow voltage drop at 160 °C; notably, the voltage drop is not as rapid as in the LE-LIB.…”
Section: Resultsmentioning
confidence: 87%
“…As high temperatures accelerate chemical degradation, the marginal voltage drop is also expected in ASLIBs. 21 As shown in Figure 3a, the SSE-ASLIB exhibits a slow voltage drop at 160 °C; notably, the voltage drop is not as rapid as in the LE-LIB. The dimensional stability of the SSE (LPSCl, annealing temperature 550 °C) prevents direct electrical shorting of ASLIBs even at higher temperatures.…”
Section: ■ Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, Banerjee et al reported the generation of partially oxygen-substituted P­(S/O) x units at the degraded interface of argyrodite-type Li 6 PS 5 Cl/LiNbO 3 -coated LiNi 0.85 Co 0.1 Al 0.05 O 2 using Raman spectroscopy . Ando et al suggested that the P­(S/O) x generation is a decomposed species of Li 6 PS 5 Cl; therefore, the P­(S/O) x unit can be assigned to a new peak. Although Li 3 PO 4 may be formed, we suggest that the main cause of the P–O bond is not likely owing to the absence of Li 3 PO 4 crystal peaks in the ED pattern (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Lithium argyrodites, Li 6 PS 5 X (X = Cl, Br, I), which exhibit low cost and high ionic conductivity (above 1 mS cm −1 ) at room temperature, make them a promising group of SSEs. [ 132 ] The Li 6 PS 5 X argyrodite is derived from the archetypal mineral argyrodite (Ag 8 GeS 6 ) with a cubic structure and a space group of F 4¯$\bar{4}$ 3m . [ 133 ] In the structure of Li 6 PS 5 X, the S atoms occupy 4a and 4c Wyckoff positions and the Li ions occupy 48 h positions.…”
Section: Specific Applications Of Defects In Lithium Batteriesmentioning
confidence: 99%